Effects of leuprorelin for the treatment of recurrent gynecological cancer by assessment including self‐administered quality‐of‐life questionnaire. Issue 1 (16th August 2018) - Tsubamoto, Hiroshi; Ueda, Tomoko; Inoue, Kayo; Isono‐Nakata, Roze; Saeki, Shinichiro; Kato, Yu; Shibahara, Hiroaki
Abstract: Aim: To investigate the effects of leuprorelin using a self‐administered quality‐of‐life (QOL) questionnaire in patients with recurrent gynecological cancer. Methods: Records of patients who received 3.75 mg leuprorelin every 4 weeks for the treatment of recurrent gynecological cancer were retrospectively reviewed. The physical domain of the QOL questionnaire, Care Notebook, was used to assess physical symptoms. Symptom deterioration was defined as a ≥10‐point increase in baseline score; otherwise, symptoms were defined as controlled. Radiological and serological responses were evaluated according to the 2011 Gynecological Cancer Intergroup criteria. Results: From 2007 to 2015, 25 patients were administered leuprorelin for the treatment of epithelial ovarian cancer, granulosa cell tumor, endometrial cancer, endometrial stromal sarcoma and clear cell cervical cancer (in 13, 3, 6, 2 and 1 patients, respectively). Twenty patients had received a median of three lines (range 1–12 lines) of chemotherapy. Ten patients had progressive disease during their previous round of chemotherapy. Twenty patients completed the questionnaire every 4 weeks. Following leuprorelin treatment for 8 weeks, the symptom and disease control rates were 65% (13/20) and 44% (11/25), respectively. Two patients, one each with granulosa cell tumor and endometrial cancer, had stable disease at 6 months. Among the 20 patients who completed the QOL questionnaire, symptom control and disease control at 8 weeks showed a significant correlation ( P = 0.016). Conclusion: Leuprorelin had minimal anticancer activity. The physical domain of the QOL questionnaire could be used to assess effects of hormonal treatment.